"Biases" in Adaptive Natural Resource Management. Issue 6 (6th July 2015) - Iftekhar, Md Sayed; Pannell, David J
Abstract: Uncertainties about the consequences of natural resource management mean that managers are required to make difficult judgments. However, research in behavioral economics, psychology, and behavioral decision theory has shown that people, including managers, are subject to a range of biases in their perceptions and judgments. Based on an interpretative survey of these literatures, we identify particular biases that are likely to impinge on the operation and success of natural resource management. We discuss these in the particular context of adaptive management, an approach that emphasizes learning from practical experience to reduce uncertainties. The biases discussed include action bias, the planning fallacy, reliance on limited information, limited reliance on systematic learning, framing effects, and reference‐point bias. Agencies should be aware of the influence of biases when adaptive management decisions are undertaken. We propose several ways to reduce these biases.